EP.FRI.9Meta-analysis of mortality risk in octogenarians undergoing emergency General Surgery operations. (28th October 2021) - Hajibandeh, Shahab; Hajibandeh, Shahin; Antoniou, George A; Antoniou, Stavros A
Abstract: Aims: To quantify the risk of perioperative mortality in octogenarians undergoing emergency general surgical operations and to compare such risk between octogenarians and non-octogenarians. Methods: A systematic review was performed in accordance with the PRISMA statement standards to identify studies reporting the mortality risk in patients aged over 80 years undergoing emergency general surgery operations. The certainty of evidence was assessed using the GRADE system. Random-effects models were applied to calculate pooled outcome data. Results: Analysis of 66701 octogenarians from 22 studies showed that the risk of 30-day mortality was 26% (95% CI 18-34%) for all operations;29% (95% CI 25-33%) for emergency laparotomy, 9% (95% CI 1-23%) for non-laparotomy emergency operations;21% (95% CI 13-30%) for colon resection;17% (95% CI 11-25%) for small bowel resection;9% (95% CI 7-11%) for adhesiolysis;6% (95% CI 5.9-6.8%) for perforated ulcer repair;3% (95% CI 2.6-4%) for appendicectomy;3% (95% CI 2.8-3.3%) for cholecystectomy;5% (95% CI 0.2-14%) for hernia repair. When stratified based on ASA status, the risk was 11% (95% CI 4-20%) for ASA 2, 22% (95% CI 10-36%) for ASA 3, 39% (95% CI 29-48%) for ASA 4, and 94% (95% CI 77-100%) for ASA 5. The  risk was higher in octogenarians compared with non-octogenarians (OR:4.07, 95% CI 2.40-6.89),  patients aged 70-79 (OR:1.21, 95% CI 1.13-1.31), and patients aged 50-79 (OR:2.03, 95% CI 1.68-2.45). Conclusions: The risk of perioperative death in octogenarians undergoing emergency general surgical operations is higher than the risk in younger patients. Laparotomy, bowel resection, and ASA status above 3 carry the highest risk.